2019
DOI: 10.1038/s41598-019-50406-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between preoperative high intraocular pressure and retinal nerve fibre layer thinning after glaucoma surgery

Abstract: Recent reports show varying results regarding peripapillary retinal nerve fibre layer (RNFL) thickness after intraocular pressure (IOP)-lowering glaucoma surgery. We hypothesised that different levels of the preoperative IOP influence RNFL thickness. A total of 60 patients (60 eyes) with glaucoma, who underwent glaucoma surgery and had a stable postoperative mean IOP < 22 mmHg, were enrolled. The RNFL thickness was measured using spectral domain optical coherence tomography, before and at 3–6 months after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 45 publications
1
10
0
4
Order By: Relevance
“…Chua et al found a decrease in the mean RNFL thickness of −4.2 ± 0.3 µm/year during the first year after TE in 105 eyes [ 45 ]. Similar to our results as regards RNFL thickness and visual field indices, Kim et al demonstrated a significant RNFL thickness reduction, but no concomitant change in the mean deviation of standard automated perimetry after 12 months of follow-up after TE or Ahmed glaucoma valve implantation [ 46 ]. In addition, further multivariate analysis revealed an association between glaucoma severity indices with postoperative loss of RNFL thickness (e.g., higher IOP, larger baseline visual field defects) [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Chua et al found a decrease in the mean RNFL thickness of −4.2 ± 0.3 µm/year during the first year after TE in 105 eyes [ 45 ]. Similar to our results as regards RNFL thickness and visual field indices, Kim et al demonstrated a significant RNFL thickness reduction, but no concomitant change in the mean deviation of standard automated perimetry after 12 months of follow-up after TE or Ahmed glaucoma valve implantation [ 46 ]. In addition, further multivariate analysis revealed an association between glaucoma severity indices with postoperative loss of RNFL thickness (e.g., higher IOP, larger baseline visual field defects) [ 46 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, the changes in RNFL-thickness compared to baseline values did not show a statistically significant correlation with either IOP change or the change in mean visual field defects over the follow-up period. Other groups also found no statistically significant correlation between RNFL change and IOP change during follow-up after drug- and/or surgery-induced IOP reductions [ 40 , 41 , 42 , 46 ]. Therefore, the data presented here cannot answer the question as to whether the mean defect of standard automated perimetry or the RNFL thickness measured by SD-OCT determines if a performed surgical intervention was a success or not.…”
Section: Discussionmentioning
confidence: 99%
“… 18 , 40 Kim et al showed a significant reduction of average RNFL thickness in the early postoperative period for different glaucoma types. 41 In primary angle closure glaucoma (PACG) RNFL damage patterns were found to be different in acute and chronic IOP elevated courses. In acute PACG, a swelling and thickening of the peripapillary RNFL right after an acute IOP elevation was observed, which resulted in thinning and atrophy over time.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors stated no significant changes of RNFL thickness after TE in short follow-up periods of 6 to 12 months [ 22 , 25 , 26 ]. However, other studies showed significant RNFL changes for 12 to 18 months after different glaucoma surgeries [ 23 , 24 , 27 ]. Kim et al found a significant RNFL thinning 12 months after TE or Ahmed valve implantation.…”
Section: Discussionmentioning
confidence: 94%
“…Schargus et al also revealed stable visual field indices during the first 24 months after TE or XEN or XEN combined with cataract surgery in POAG eyes naïve to glaucoma surgery [ 20 ]. Kim et al demonstrated stable visual field indices although further statistically significant RNFL decrease during the first 12 months after TE or Ahmed valve implantation [ 24 ]. A lack of direct correlation between defect depth and RNFL thickness could also be due to the decreasing relevance and informative value of OCT examination with progressive damage.…”
Section: Discussionmentioning
confidence: 99%